MENIMBANG KEBIJAKAN NASIONAL DAN GLOBAL DALAM PENDIDIKAN ISLAM: KAJIAN LITERATUR REVIEW TERHADAP IMPLEMENTASI DAN RELEVANSI UU SISDIKNAS DI ERA GLOBALISASI - Luvianingtias, Shera Nabila; Lestari, Rahayu; Romlah, Romlah; Abdurrahman, Abdurrahman; Junaidah, Junaidah (STKIP Pesisir Selatan, 2025)
This study aims to examine the relevance and implementation of Law Number 20 of 2003 concerning the National Education System (UU Sisdiknas) within the context of globalization in Islamic education in Indonesia. Using a critical literature review approach, this research analyzes national and international publications from the last five years to evaluate the relationship between national education policies and global demands. The findings reveal that globalization has significantly influenced the direction of Islamic education policies, particularly in adapting to technological, economic, and socio-cultural developments. Although the UU Sisdiknas provides a legal framework for integrating Islamic education into the national education system, its implementation still faces several challenges, such as the lack of alignment between Islamic spiritual values and global competencies, weak institutional coordination, and limited digital readiness. Therefore, the development of Islamic education policies should be directed toward achieving a balance between spirituality and modernity by emphasizing curriculum innovation, teacher professionalism, and adaptive governance so that Islamic education can remain competitive while preserving its foundational Islamic values.